Synthesis of CoNi by Electrodeposition Technique and its Application as an Electrocatalyst for Water Splitting - Chika Shafa Maura; Muhammad Fathar Aulia; Raudhatul Hadawiyah; Wulan Kharisma Dera; Hilman Syafei (Chemistry and Materials, 2023)
Water splitting is regarded as a highly efficacious methodology for obtaining hydrogen, intending to be employed for the purpose of renewable fuel production. However, the performance of this technique is constrained by the sluggish kinetics of the hydrogen evolution reaction in alkaline environments and the oxygen evolution reaction, which leads to significant energy inefficiency and excessive potential requirements. To enhance the reaction kinetics and efficiency of water splitting, there exists a pertinent requirement for an electrocatalyst that exhibits commendable efficiency. The primary objective of this study is to construct a cobalt-nickel (CoNi) electrocatalyst that facilitates water splitting. The present study employs the technique of electrodeposition for its experimental procedures. The findings of the study indicated that the CoNi sample, as observed through scanning electron microscopy with energy dispersive X-ray spectroscopy (EDX) analysis, exhibited a flattened, circular form and agglomeration. The EDX analysis yielded elemental composition results indicating a cobalt content of 20.51% and nickel content of 79.49% The X-ray diffractometer analysis reveals that the CoNi metal alloy has manifested a crystalline structure with a cubic configuration. The electrochemical impedance spectroscopy found that the charge transfer resistance of CoNi with the electrolyte solution was 1.48 kΩ. The data collected from the chronoamperometry test indicates the presence of a consistent and unchanging electrical current. Additionally, the cyclic voltammetry test presented Epa and Epc values of 0.4469 V and 0.3037 V, respectively, leading to a calculated ∆E of 0.1432 V. The research findings establish that the CoNi alloy, synthesized via the electrodeposition technique, exhibited a performance-effective electrocatalyst that closely approached the desired outcome.